Agentes infecciosos enteroparasitários associados a indivíduos estomizados - Santos, Cibele Velleda dos (2011)
The intestinal parasitoses or enteroparasitoses are a serious public health problem particularly in developing countries. Meantime, there are several studies that wrap the prevalence and the incidence of parasitoses in several populations, lacking parasitological investigations involving individuals with a intestinal ostomy. This study aimed to investigate the presence of infectious nature of parasitic diseases in individuals with ostomy enrolled in an Ostomy Program of the Department of Health and Management of the SUS in the city of Pelotas, RS. A questionnaire was given to patients for epidemiological evaluation of demographic, social, and cultural issues that would limit the subjects' knowledge about the parasites. Totaled to 71 individuals also submitted to parasitological tests using the methods of Faust and Ritchie modified Baermann-Moraes. Were collected and analyzed 03 samples per individual. The prevalence of carriers was 5.6%, all by monoparasitism. Among pacients positives were detected in the same proportion (25%), larvae of Enterobius vermicularis eggs of Taenia sp. eggs Enterobius vermicularis and larvae of Strongyloides stercoralis. Among participants, 49.3% were being female and 50.7% male. 76.1% had colostomy and 23.9% had ileostomy. Of the operations for stoma intestinal was necessary 37.1% due to the rectum cancer, 24,3 % for cancer of colon and 15.7% resulting from other intestinal diseases. As to knowledge about parasitic diseases, 69 % of the interviewed ones revealed to know the subject, 56.3% of the individuals showed up the importance of the hygiene of the hands, nails, sets of cutlery and foods, including his appropriate cooking.Meantime, 33.8% of the interviewed ones did not know how will be careful to prevent the intestinal parasitoses, and, even so, 50.7% of the individuals not feel to miss bigger of explanation regarding the approach in question.